A Qualitative Evaluation of Clinical Audit in UK Dental Foundation Training - Peter Thornley; Alyson Quinn (MDPI AG, 2017)
Clinical Audit (CA) has been recognized as a useful tool for tool for improving service delivery, clinical governance, and the education and performance of the dental team. This study develops the discussion by investigating its use as an educational tool within UK Dental Foundation Training (DFT). The aim was to investigate the views of Foundation Dentists (FDs) and Training Programme Directors (TPDs) on the CA module in their FD training schemes, to provide insight and recommendations for those supervising and undertaking CA. A literature review was conducted followed by a qualitative research methodology, using group interviews. The interviews were transcribed and thematically analyzed using NVIVO, a Computer-Assisted Qualitative Data Analysis tool. CA was found to be a useful tool for teaching management and professionalism and can bring some improvement to clinical practice, but TPDs have doubts about the long-term effects on service delivery. The role of the Educational Supervisor (ES) is discussed and recommendations are given for those supervising and conducting CA.